Does public governance always matter? How experience of poor institutional quality influences FDI to the South - Julia Darby; Rodolphe Desbordes; Ian Wooton (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates whether the higher prevalence of South multinational enterprises (MNEs) in risky developing countries may be explained by the experience that they have acquired of poor institutional quality at home. We confirm the intuition provided by our analytical model by empirically showing that the positive impact of good public governance on foreign direct investment (FDI) in a given host country is moderated significantly, and even in some cases eliminated, when MNEs have been faced with poor institutional quality at home.
Keywords: F22; 330; South-South FDI; public governance; institutions; Direktinvestition; Multinationales Unternehmen; Standortfaktor; Institutionelle Infrastruktur; Good Governance; Süd-Süd-Beziehungen; Entwicklungsländer